2015
DOI: 10.19128/turje.44440
|View full text |Cite
|
Sign up to set email alerts
|

The role of achievement goal orientations and interest on metacognitive strategy use of preservice science teachers

Abstract: The purpose of this study was to determine contribution of achievement goal orientations and personal interest on prediction of metacognitive strategy use of preservice science teachers. This study was conducted with three hundred and twenty-two preservice science teachers who are freshmen, sophomore, junior and senior of elementary science education program. Data was collected by using three instruments which are "Metacognitive Self-Regulation Subscale ofMotivated Strategies for Learning Questionnaire", "Achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…According to Renninger and Hidi (2011), there are two types of interest: situational and individual. Individual interest is consistent, stable and includes delight, personal significance, a preference for a subject, and an allaround preference for a certain field (Atasoy, 2015;Renninger & Hidi, 2011). Conversely, situational interest refers to a state of alertness and affective reaction at a specific moment in the environment that may be prompted by an environmental stimulus that may or may not be persistent (Laine, 2019;Renninger & Hidi, 2011).…”
Section: Levels and Differences In Mathematics Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Renninger and Hidi (2011), there are two types of interest: situational and individual. Individual interest is consistent, stable and includes delight, personal significance, a preference for a subject, and an allaround preference for a certain field (Atasoy, 2015;Renninger & Hidi, 2011). Conversely, situational interest refers to a state of alertness and affective reaction at a specific moment in the environment that may be prompted by an environmental stimulus that may or may not be persistent (Laine, 2019;Renninger & Hidi, 2011).…”
Section: Levels and Differences In Mathematics Interestmentioning
confidence: 99%
“…Interest is a concept that researchers have recently picked interest in to understand the process and outcomes of learning (Atasoy, 2015). Promoting interest in education is a priority for educational institutions, particularly in mathematics, where secondary school students have a low level of interest (Xu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Goal setting should be a decisive factor in determining a student's academic success. For instance, Atasoy (2015) demonstrated that mastery goals, whereby students are motivated by the intrinsic value of learning predict the adoption of metacognitive strategies (i.e., methods which focus on understanding the learning process), which influence students' learning level. Similarly, Pintrich (2000b) stressed that those goal settings should determine students' study experiences in terms of affect and strategy use.…”
Section: Motivation Theoriesmentioning
confidence: 99%
“…To understand the process and results of learning, scholars have recently taken an interest in the concept of interest (Atasoy, 2015). According to Renninger and Hidi (2011), interest develops as a result of a person's engagement with his environment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Renninger and Hidi distinguished between two categories of interest: situational interest and individual interest. According to Atasoy (2015) and Renninger & Hidi (2011), an individual's interest is a consistent, enduring quality that includes enjoyment, personal importance, a preference for a topic, and a general liking of a particular field. On the other hand, situational interest describes a state of attentiveness and an affective response at a certain moment in the environment that may be generated by an environmental stimulus that may or may not be persistent (Laine, 2019;Renninger & Hidi, 2011).…”
Section: Introductionmentioning
confidence: 99%